Enhancement of polymerase chain reaction using graphene nano-flakes - Rasheed, Abdul Khaliq; Kafafy, Raed Ismail; Faris, Waleed Fekry; Mohd. Salleh, Hamzah (2011)
The excellent heat transfer properties of nanoparticles have potential applications in various fields including biology during the last two decades. Recently, the use of various nanoparticles in polymerase chain reaction (PCR) resulted in significant enhancement of its efficiency and specificity. In this research we have demonstrated the effects of a novel material, graphene nano-flakes on PCR. The rationale behind the use of graphene flakes is its unique physical and heat transfer properties. A number of experimental results including the effect of graphene flakes on denaturation of DNA and annealing step will also be discussed. The preliminary results clearly show that enhanced heat transfer effect of nano-flakes augment PCR yield and ultimately overall enhancement in reaction efficiency.